Phytochemical analysis and in-vitro antiurolithiatic properties of selected Malaysian herbs - Wan Marzuki Rashidi, Wan Nur Ain Syukriah; Muhammad, Norhayati; Sairi, Nur Halimah; Abdul Rahim, Nur Fazira; A. Talip, Balkis; Abdullah, Norazlin; Abu Bakar, Mohd Fadzelly (Penerbit Akademia Baru, 2019)
The aim of this study was to investigate the phytochemical content of selected Malaysian herbs and their potential antiurolithiatic effects using in-vitro method. The herbs involved are Ceiba pentandra, Cymbopogon citratus, Euphorbia hirta, Melastoma malabathricum and Ortosiphon stamineus. Aqueous extracts of each herbs were prepared through decoction while Standard drugs Cystone, was used as positive control in comparison. Qualitative analysis was carried out to detect phytochemical presence and nucleation assay to investigate their inhibition effects towards calcium oxalate crystallization urolithiasis in vitro. Based on results, the same trends were observed between phytochemical content and inhibition rate of calcium oxalate crystallization. O. stamineus extract (73.48%) which showed the highest inhibition rate hold the most phytochemical content. while the lowest inhibition rate was occupied by C. citratus extract (45.45%) with the least phytochemical content. The high amount of phytochemicals particularly saponin followed by steroid and terpenoid in O. stamineus extract might contributes to the high inhibition activities of calcium oxalate crystallization as compared to low amount of phytochemicals observed in C. citratus extract. It can be concluded that O. stamineus possesses highest inhibition percentage against calcium oxalate which could be attributed to its saponins, tannins, steroid and terpenoid content.